Komunikasi Fatis Dakwah Caknunquotes dalam Media Sosial Instagram - Armaza-Faraba, Karina Sofiananda; Sumarlam, Sumarlam; Purnanto, Dwi (Jurnal Komunikasi Islam, 2020)
This article discusses the form and function of pro-selytizing phatic communication on the Instagram account vi-deo @caknunquotes. By using descriptive qualitative methods through the techniques of listening and note taking, the study found that most of the categories in da’wa on the Instagram video @caknunquotes carried a lot of regional elements or re-gional dialects in the form of particle fat, fatic words, and fatic phrases. With regard to phatic communication function, it expresses courtesy to the congregation, convinces the congre-gation, confirms the contents of the da'wah, asks for approval, greetings to familiarize themselves, as a form of proof of the intent or contents of the preaching, Javanese expression, as emphasis on the sentence sentence, and as a form of clarifying the contents again propaganda. In addition, flabby communi-cation with dialect or local language style makes the speech partner more deeply the contents of his da'wah.